Bilobate leaves of Bauhinia (Leguminosae, Caesalpinioideae, Cercideae) from the middle Miocene of Fujian Province, southeastern China and their biogeographic implications - Lin, Yanxiang (BMC Evol Biol, 2015)
BACKGROUND: Morphological and molecular phylogenetic studies suggest that the pantropical genus Bauhinia L. s.l. (Bauhiniinae, Cercideae, Leguminosae) is paraphyletic and may as well be subdivided into nine genera, including Bauhinia L. s.s. and its allies. Their leaves are usually characteristic bilobate and are thus easily recognized in the fossil record. This provides the opportunity to understand the early evolution, diversification, and biogeographic history of orchid trees from an historical perspective under the framework of morphological and molecular studies. RESULTS: The taxonomy, distribution, and leaf architecture of Bauhinia and its allies across the world are summarized in detail, which formed the basis for classifying the bilobate leaf fossils and evaluating the fossil record and biogeography of Bauhinia. Two species of Bauhinia are described from the middle Miocene Fotan Group of Fujian Province, southeastern China. Bauhinia ungulatoides sp. nov. is characterized by shallowly to moderately bilobate, pulvinate leaves with shallowly cordate bases and acute apices on each lobe, as well as paracytic stomatal complexes. Bauhinia fotana F.M.B. Jacques et al. emend. possesses moderately bilobate, pulvinate leaves with moderately to deeply cordate bases and acute or slightly obtuse apices on each lobe. CONCLUSIONS: Bilobate leaf fossils Bauhinia ungulatoides and B. fotana together with other late Paleogene – early Neogene Chinese record of the genus suggest that Bauhinia had been diverse in South China by the late Paleogene. Their great similarities to some species from South America and South Asia respectively imply that Bauhinia might have undergone extensive dispersals and diversification during or before the Miocene. The fossil record, extant species diversity, as well as molecular phylogenetic analyses demonstrate that the Bauhiniinae might have originated in the Paleogene of low-latitudes along the eastern Tethys Seaway. They dispersed southwards into Africa, migrated from Eurasia to North America via the North Atlantic Land Bridge or floating islands during the Oligocene. Then the genus spread into South America probably via the Isthmus of Panama since the Miocene onward, and underwent regional extinctions in the Boreotropics of mid-high-latitudes during the Neogene climatic cooling. Hence, Bauhinia presently exhibits a pantropical intercontinental disjunct distribution. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12862-015-0540-9) contains supplementary material, which is available to authorized users.